Cloud-network convergence solution based on SRv6 - Wei WANG; Peng WANG; Xiaoyu ZHAO; Honglei XU (Dianxin kexue)
The development background and requirements of cloud-network convergence were introduced, and the principle and advantages of SRv6 technology were explained.At the same time, cloud-network convergence solutions based on SRv6 was proposed, and the technical architecture was studied, including SD-WAN, cross domain networking, cloud service and cloud interconnection.By comparing the traditional solution with the solution based on SRv6, the advantages of the latter in solving the existing cloud network business pain points were explained, and the significance of cloud-network convergence was described.